Characteristics and prognosis of children with recurrent T-cell acute lymphoblastic leukemia: a long-term follow-up report in China. Issue 14 (6th December 2022) - Liu, Xiaoming; Zou, Yao; Zhang, Li; Zhang, Yingchi; Chen, Yumei; Chen, Xiaojuan; Guo, Ye; Yang, Wenyu; Zhu, Xiaofan
Abstract: This study assessed the relapse characteristics and prognosis of 145 children newly diagnosed with T-cell acute lymphoblastic leukemia (T-ALL). The overall complete response (CR) rate was 91.7% (133/145), and the overall recurrence rate was 31.6% (42/133). The recurrence rate in the intermediate-risk (IR) group and high-risk (HR) group was 15.4% and 47.1%, respectively ( p  < 0.001). Patients with young age, early T-cell precursor ALL, central nervous system (CNS) involvement, TCRγ gene rearrangement, karyotypic abnormalities, or absence of TCRβ gene rearrangement ( p  < 0.05) tended to relapse. All recurrences occurred within 36 months after diagnosis. The HR group recurred earlier than the IR group ( p = 0.026). The 3-year overall survival (OS) rate was significantly lower in the HR group than in the IR group ( p  < 0.001). All relapsed children died within 12 months after recurrence. Early intervention may benefit children with a high risk of recurrence.